Unveiling the Role of Prolactin and its Receptor in Male Reproduction - Raut, Sanketa; Deshpande, Sharvari; Balasinor, Nafisa H. (Hormone and Metabolic Research, 2019)
Prolactin is a peptide hormone known to have multiple functions. However, the role of prolactin has been extensively studied only in female physiology and its function in male reproduction still remains majorly unexplored. Studies in rodents and humans have demonstrated the presence of prolactin and its receptor in testes, thereby suggesting a possible role during spermatogenesis. Experimental evidences from prolactin and prolactin receptor deficient male rodent models as well as studies done in hypo- and hyper-prolactinemic males hint at neuroendocrine and reproductive abnormalities. Nonetheless, there still remains a lot of ambiguity on the exact role of prolactin and its receptor in male reproduction. This review summarizes in depth on the role of prolactin in spermatogenesis.
Keywords: prolactin; prolactin receptor; spermatogenesis; testis; male reproduction